UPAYA PENGEMBANGAN KECERDASAN SPIRITUAL SISWA MELALUI KEGIATAN EKSTRAKURIKULER ROHANI ISLAM DI SMP YAPAN INDONESIA, DEPOK - Gamar Al Haddar (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
This study aims to determine (1) the state of the Islamic spiritual extracurricular activities of SMP Yapan Indonesia. (2) a state of spiritual intelligence in junior high school students of Yapan Indonesia (3) efforts in the development of spiritual intelligence Yapan Indonesian junior high school students through extracurricular activities spiritual Islam. This research was conducted using qualitative research methods. In determining the sample, the researcher use purposive sampling, and the "snowball" technique. The main instrument in this study were researchers. Information about the research themes were explored by the investigators through participatory observation techniques, interviews, literature and documentation. The validity of the data tested credibility through the extension of participation, persistence observation, tringulasi, peer discussion and the adequacy of reference and transferability, dependability and confirmability The results of this study concluded the following matters that (1) Various activities in extracurricular activities Rohis, starting from the daily program, weekly program and annual program to support the development of spiritual intelligence of junior high school students in Yapan Indonesia. (2) Characteristics of junior high school students in Yapan Indonesia which has a spiritual intelligence is high, demonstrated by the following namely: the student is able to resolve this problem without emotion, the students were able to comply with the existing regulations, students are able to develop their creativity, the students are able to reflect on the problems faced and students are able to act positively oriented values of Godhead. (3) A number of efforts made by the extracurricular activities Rohis, in developing spiritual intelligence student, pursued through: (a) changing the personality of the students better, (b) foster students' creativity in developing potential, (c) foster social caring , (d) foster self-reflection on the problems faced, (e) raising the awareness level of students that have clear purpose in life with the mission and vision in life, and (f) foster the attitudes of students to act positively oriented values of Godhead.